Mental toughness and its relationship to shooting accuracy in the 10m air pistol among the national youth team players - Abbas, Asst.L. Saud Taha; Abdulhadi, Prof. Dr. Haider Mohammed (Sulaimani Journal for Humanities, 2026)
Modern psychology plays a significant role in sports in general and Olympic shooting events in particular. While motor skills (technique) play a direct and crucial role in achieving optimal performance in most events, technique alone is not the sole factor in developing athletic ability. Several other important factors, including the psychological qualities required for the sport, also contribute. This research aims to determine the contribution of mental toughness to performance in air pistol shooting accuracy. The researcher employed a descriptive methodology using survey and correlational approaches, deemed most suitable for the nature of the study. The research sample consisted of four members of the national youth team participating in the air pistol event at the Khawla Bint Al-Azwar shooting range in Baghdad. A mental toughness test and an accuracy test were administered to the participants. The researchers concluded that mental toughness has a positive effect on improving air pistol shooting accuracy.
Keywords: Mental toughness; aiming accuracy; air pistol